Parental depression and parent and child stress physiology: Moderation by parental hostility. Issue 8 (23rd August 2017) - Merwin, Stephanie M.; Leppert, Katherine A.; Smith, Victoria C.; Dougherty, Lea R.
Abstract: This study examined the moderating role of parental hostility on the associations between parental depression and the cortisol awakening response (CAR) and morning cortisol levels of both parents and children. 148 parents and 148 preschool‐aged children provided salivary cortisol samples at waking, 30 and 45 min post‐waking on two consecutive days. Parental depression was assessed using a clinical interview, and parental hostility was assessed using an observational parent‐child interaction task. Results indicated that the combination of parental lifetime depression and high parental hostility was associated with lower morning cortisol levels in both parents and children. This interactive effect was present in children regardless of their exposure to parental depression. In addition, the combination of higher levels of parents' current depressive symptoms and parental hostility was associated with lower parent CAR. Lastly, parents' and children's lower morning cortisol levels were associated with parent‐reported child externalizing symptoms. Findings demonstrate that parents and children have similar stress system functioning related to parental depression and the parenting context, as well as children's behavioral problems, which may play a role in the intergenerational transmission of risk for psychopathology.